Karakteristik dan Perilaku Berisiko Pasangan Infertil di Klinik Fertilitas dan Bayi Tabung Tiara Cita Rumah Sakit Putri Surabaya - Najakhatus Sa’adah; Windhu Purnomo (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
Infertility is a condition in which someone unable to conceive and give birth after one year of regular coital activity without contraception. The aim of this study was to describe respondents characteristic of infertile couple and risk factors of the incidence of infertility, which are smoking, alcohol consumption and obesity on the incidence of infertility. This study used descriptive analysis method. Sample of this study were all patients of infertile couples in the Fertility Clinic and In Vitro Fertilization Tiara Cita during the period from November to December 2015. They were 83 couples as the samples. The data of this study were collected from questionnaires as primary data and general at clinic as secondary data. Analysis of data through cross tabulation. The results showed that respondents was conduct risk behavior (39,8 percent ) to smoke, alcohol consumption (27,7 percent), and obesity (40,9 percent). Based on this data showed that the majority of couples infertil at the clinic was behave that the risk is one factor of infertility. The need for increased knowledge about risk factors and for couples who had obesity to applied a pattern of a healthy diet by keeping weight ideal.